Waqf and Impact Sustainable Finance in Indonesia: Lessons from ESG Reporting Concept - Nur - Arifah; Putri Maulidiah; Lu'liyatul Mutmainah; Lisa Listiana (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction to The Problem: The expansion of waqf institutions in Indonesia is increasingly promising. However, not many implement a strict reporting system. Moreover, most of the waqf institutions are managed by Nazhir individually. The application of ESG reporting is important to see how a waqf institution is seen as having an impact on a number of issues related to the existence of the institution in the context of sustainable finance. Purpose: Environmental, social, and governance (ESG) reporting is one method of reporting the sustainable impact of a company's performance as measured in a number of analytical tools. This study aims to reveal ESG aspects in reporting by waqf institutions. Design/Methodology/Approach: This study employs a qualitative approach by utilizing a meta-synthesis of ESG literature. This is a systematic exploratory research strategy for building or extracting references from qualitative research. Findings: This research found that ESG concept is also relevant to be applied in philanthropic institutions such as waqf institutions in Indonesia. Maqashid sharia is the principle in Islamic institution that mandates transparency and responsibility not only to the community, but also to the surrounding environment to realize modern organizational governance.